The brand audit of Ovaltine - Suppakarn Riwthong; Levermore, Roger; Zimmerman, Willi; Tocquer, Gerard; Royal Thai Government; Asian Institute of Technology Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Ovaltine has been on the Thai market of malt chocolate beverages for children for more than 30 years. However, a new generation of customers is unaware of the brand, and they have problems with the other products where they have a different target. My internship at KANTAR enhanced the ability to examine and research this issue in depth where I had been involved with the project of Ovaltine brand analysis. The report's objectives are to examine the current Ovaltine advertisement, its target audience, and positioning, to profile potential Ovaltine brand customers, and to highlight and offer potential communication channels. The conclusions are based on the results of a quantitative data questionnaire provided by the KANTAR team, and it is used to evaluate the performance of Ovaltine's advertising. To analyze and give the recommendation, I used the brand audit approach where the focus will be on brand communication. Followed by the digital marketing tools and content marketing for the social media campaign which will be the core of my recommendations for Ovaltine. According to the findings of this internship report analysis, Ovaltine has a wide range of products to meet the needs of its customers. However, because of their marketing and advertising approach, these products are overshadowed by Ovaltine Original, leaving a significant possibility for potential customers untapped. It must be mentioned that, although having very strong awareness and marketing performance, with customers are willing to buy the items, Ovaltine's sales are shrinking compared to their competitors in the same market.
An Internship Report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Internship Report (M. BA.) - Asian Institute of Technology, 2022
Keywords: Advertising -- Brand name products; Brand name products -- Marketing; Social media -- Marketing